Poder americano e estados nacionais: uma abordagem a partir das esferas econômica e militar - Almeida, Fernando Chaves (2006)
The main objectives of this dissertation are: in first place, to rescue the historical perspective of the term Imperialism, as argued for its classic authors, inquiring if the quarrels of a century behind, and its categories, possess some validity in the capitalism that we live deeply in the present time; in according to place, to argue the meaning and the validity of concepts as strategy and hegemony, mainly working in such a way how much economic the military sphere, and its inter-relations. This for, after that, showing to the paper of the economic policy of U.S.A. in the global scene (Inter-relations with State-National) and the emanation of its power; e finally, to inquire if is necessary to exist an eventual confrontation between the spheres economic and geopolitical-military, or if the military power is only the pack of the persecution of the imperial project of U.S.A., that in its essence is basically economic. The used methodology was based on bibliographical research. The conclusions point with respect to the fact of that the Imperialism of modernity would be involved by a militarism that would be pack of the dynamics of the system, whose center shelters a species of being able coercitive established in the economic mediation of the market, and that the more next the system if points out of an imperial configuration, more close to the collapse it will be, therefore he would destroy the proper dynamics that it gives sustentation: the competition between national state-economies.